Separation According to Ibn Hazm’s View in The Ring of the Dove: An Applied Study in the Eras of the Taifas And Almoravids - Kadhim, Anaam Mustafa; Al-Majdi, Khalid Abdul Kadhim (Journal of Ecohumanism, 2025)
This research sheds light on the scourge of separation and its moral effects on lovers, especially the lover, and the feelings he experiences during and after this situation, or his obsessions with it. It is based on Ibn Hazm’s view of the diversity of this situation between abandonment, separation, and behavior, and his treatment of the various aspects of platonic love. Separation was a psychological and poetic resource for poets to express their suffering and experiences through their poems about separation.